"Whatever gain I had ...": Ethnicity and Paul"s self-identification in Philippians 3:5-6 - Duling, Dennis (HTS teologiese studies, 2008)
This study is not an exercise in Vernon Robbin’s groundbreaking socio-rhetorical criticism as put forth in his impressive The Tapestry of Early Christian Discourse and Exploring the Texture of Texts. It does have much in common with his “social and cultural texture”. It also touches “inner texture” in relation to Paul’s implied argument, “intratexture” with respect to the implied importance of scripture for Paul, and “ideological texture” in relation to Paul’s statements about the righteousness of God, millennial hopes, and ethical norms in contrast with his ethnic identify. These suggestions only scratch the surface of possibilities for using socio-rhetorical criticism to interpret ethnicity in Philippians. Social-rhetorical critics, I trust, will see even more socio-rhetorical potential for this subject than I have mentioned. Indeed, I hope that it stimulates such analysis.